Piracy in University: Factors associated with digital piracy among multimedia students - Anawar, Syarulnaziah; Ayop, Zakiah; Othman, Nur Fadzilah; Ding, Chiu Sin; Hassan, Aslinda; Mohd Ali, Nor Raihana (Little Lion Scientific Islamabad Pakistan, 2021)
Internet is especially important during the Covid-19 pandemic, where there is wide adoption of an online learning platform for teaching and learning. Students always utilize the Internet in many ways to meet their academic needs. Therefore, considerable attention has been given to the problem of digital piracy behavior among university students. This study aims to investigate the factors to be considered as part of digital piracy behavior among multimedia students. Guided by a theoretical perspective from Deterrence Theory, Ethics Theory, and Neutralization Theory, this study adopted a quantitative methodology where data from a survey (N=200) of multimedia students in public and private universities in Malaysia is analyzed. This study proposed a model that offers understandings of the contributing factors that may influence digital piracy behavior among multimedia students. Based on the findings, this study concluded that fear of legal consequences has the highest influence on digital piracy behavior, followed by perceived likelihood of punishment and neutralization techniques. This study may benefit other researchers attempting to understand multimedia students' standpoints on digital piracy behavior and increase user awareness in the computer ethics research area